Perbanyakan Tanaman Secara Vegetatif Di Desa Pekan Kamis Kelurahan Tembilahan Barat - Mulono Apriyanto; Marlina Marlina; Muhammad Arpah (Celebes Abdimas: Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this community service program is 1) Providing new insights to youth in youth organizations about plant propagation 2) Providing insight to youth in youth organizations about garden development 3) Youth in youth organizations can provide seeds for ornamental plants and fruit plants independent. The stages in the implementation of community service programs are divided into pre-implementation and implementation. The pre-implementation stages include: 1) Field observations. 2) Stages of preparation of tools and materials. Is the preparation phase to prepare all the preparation tools and materials as training material for partners. The implementation stages include 1) Practice of making verticulture 2) Material about Propagation of ornamental plants with vegetative propagation 3) Propagation practices of fruit plants with cuttings and grafts. From the results of field observations, it is known that the problems of youth are 1) Lack of skills in park management and maintenance. The conclusion of this community service activity is that it has been able to solve the problem 1) the youth in the youth cadets are skilled in providing ornamental plant material and fruit for planting in the environment 2) the youth in the youth cadets are skilled in making a vertical garden.